ASME 2020 Heat Transfer Summer Conference 2020
DOI: 10.1115/ht2020-9018
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Stability of Direct Contact Steam Condensation

Abstract: An investigation into the conditional stability of direct contact steam condensation is presented. Direct contact steam condensation systems heat process fluids more effectively than indirect contact heat exchangers because the total energy of the steam is introduced directly into the process fluid, bypassing any resistances associated with having to cross the heat exchanger boundary. In the present work, superheated steam is injected perpendicular to a flow of subcooled liquid water. Conditional stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was found that under different flow conditions, the jet is divided into a stable condensation zone (SC), condensation oscillation zone (CO), chugging transition zone (TC), and chugging zone (C). Li et al (2019), Qiu et al (2017), Alden et al (2020), Wang et al (2019), and others have carried out research on the pressure oscillation of pure steam jets. It is found that the pressure oscillation of low water temperature is caused by the rupture of the steam bubble.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that under different flow conditions, the jet is divided into a stable condensation zone (SC), condensation oscillation zone (CO), chugging transition zone (TC), and chugging zone (C). Li et al (2019), Qiu et al (2017), Alden et al (2020), Wang et al (2019), and others have carried out research on the pressure oscillation of pure steam jets. It is found that the pressure oscillation of low water temperature is caused by the rupture of the steam bubble.…”
Section: Introductionmentioning
confidence: 99%